Epidemiology of hepatitis E virus infection - Kasem, A; Azeem, K; Vlčková, J; Zatloukalová, S; Štěpánek, L; Kyselý, Z; Kollárová, H (Epidemiologie, mikrobiologie, imunologie, 2019)
Hepatitis E is a major concern to public health, it is estimated that 44,000 people die annually due to hepatitis E. Hepatitis E virus (HEV) is the most common cause of acute viral hepatitis in the world. HEV has been found with 7 genotypes, only 4 can infect humans. Genotypes 1 and 2 are major causes of the epidemic and endemic acute hepatitis in developing countries. In the poor hygienic conditions, these genotypes are obligate human pathogens transmitted between humans by the fecal-oral route and via contaminated water. On the contrary, in developed countries, genotypes 3 and 4 are of zoonotic origin and they are transmitted by alimentary route and via direct contact with the infected animal. Transmission by blood, blood products and tissues from infected persons or animals and even mother-to-infant transmission is also possible. Hepatitis E clinical course varies from self-limiting disease to fulminant hepatic failure, and extrahepatic manifestations have occurred. Management to control and prevent this infection is mainly hygienic measures. The provision of clean drinking water and ameliorating the sanitation of human wastes are the most effective preventive approaches as in any infection outbreak transmitted through the fecal-oral route. Nevertheless, dietary habits, distribution of different zoonotic reservoirs and the hygienic level play a crucial role in limiting and preventing the spread of hepatitis E in the developed countries. Although HEV vaccine was developed, it is still available only in China. It protects against genotype 4 with no clear evidence of protection against other genotypes.
Keywords: Animals; Zoonoses; Genotype; virus hepatitidy E; zoonózy; Hepatitis E virus; China; risk factors; HEV; lidé; Hepatitis E; genotyp; epidemiology; Čína; hepatitis E; zvířata; prevention; hepatitida E; Humans